A política pública de assistência estudantil: uma análise sobre a contribuição do benefício da residência universitária para a permanência na UFPB - Lima, Fábio Danilo Rolim de (2019)
Public policies introduced with the aim of democratizing access to higher education effectively enabled the entry of historically excluded subjects, which required the expansion of policies aimed at remaining in the IFES, among them, actions that refer to student assistance through National Program of Student Assistance - PNAES. In this perspective, we defined as main objective of the research to analyze the contribution of the benefit of the university residence with regard to the stay with success of the students of the undergraduate degree of Campus I of the Federal University of Paraíba. Therefore, we have developed the following specific objectives: to characterize student assistance policy in the context of expansion and social inclusion policies in higher education; map the actions developed by PRAPE aimed at student assistance at the UFPB; to recognize the academic situation of the students benefiting from the University Residence for Men and Women (URMW); analyze the situation that is related to the academic performance of students benefiting from the URMW; and propose actions for the improvement of the academic performance of the beneficiaries of the university residence of the UFPB. This is a study under the qualitative approach of exploratory bias, which uses bibliographical and documentary research as techniques. The Integrated System of Management of Academic Activities (ISMAA) was the main instrument adopted for collection of data. The research population consisted of 362 students benefiting from the URMW in the period of 2015.2 and the sample represented 100% (one hundred percent of this universe). Thus, our research pointed out that the university residence of the UFPB was significantly contributory for 87% (eighty seven percent) of the investigated ones. In addition, some actions were proposed to the managers of the institution, aiming to improve the academic performance and the students' stay with success.